Project Management Office e Sua Contribuição para o Desempenho do portfólio de Projetos - Lagass, Scheila (2021)
Organizations increasingly create Project Management Offices (PMOs) in order to overcome the challenges of greater complexity and importance of projects and, thus, create value for organizations. Although it has been verified in the literature that the PM